Kelayakan Investasi Produksi Keripik Udang (Litopenaeaus vannamei) Menggunakan Penggorengan Vakum - Hari Ismanto; Arham Rusli (Fapetrik-UMPAR, 2020)
Investment feasibility studies are needed to determine whether a business is feasible or not to run. The shrimp chips industry utilizes shrimp raw materials which are available quite a lot in the market. Vacuum frying is a frying process at low temperatures and pressures lower than atmospheric pressure to produce healthy and high-quality food. The research objective was to determine the feasibility of investing in shrimp chips resulting from vacuum frying and to determine the sensitivity of changes in raw material input and profit deficits. The results of the investment feasibility analysis with an interest rate of 20% using a vacuum fryer with a capacity of 6 kg per process are feasible to run according to the investment feasibility analysis parameters, namely Net Present Value (NPV) IDR 119,535,863.15; Net B/C 1.94; Payback Period (PP) 1 year 9 months; Break Event Point (BEP) for IDR 211,041,152.22 and Break Event Point (BEP) for production of 703 kg. The results of the sensitivity analysis to raw material input if it increases by 10%, the investment is feasible except for the Net B/C parameter (0.26) or less than 1, and the sensitivity analysis to profits if it decreases by 10%, indicates that the investment is not feasible to run.